Aspects of enlightenment social theory and the ethics of truth - Osborne, Thomas, 1964-; ebrary, Inc. (London : UCL Press, 1998)
This is a timely, distinctive and sparkling introductory account of social theory and the central role of enlightenment within it. Osborne argues that social theory should be based on an idea of enlightenment rather than modernity.
Bibliography: p. 195-209 and includes index.
Electronic reproduction.
Keywords: Social sciences -- Philosophy; Enlightenment; Philosophy, Modern; Electronic books